A Review of Maqashid Shariah on the Use of Artificial Intelligence in Detecting the Causes of Divorce Through Social Media - Wani, Wani (AT-TAFAHUM: Journal of Islamic Law, 2025)
The development of digital technology, particularly Artificial Intelligence (AI), has brought significant changes across various fields, including family law. Al has the capability to analyze social media data to detect potential risks of divorce. This study employs a qualitative method with a normative approach through literature review, drawing on both classical and contemporary Islamic legal sources, as well as an analysis of the ethical dimensions of technology use. The aim of this article is to examine such utilization from the perspective of maqasid al-shariah. The study explores relevant principles of Islamic law concerning divorce and the preservation of family welfare in an increasingly digital era. The findings indicate that, from a technical standpoint, Al can assist in identifying patterns of interaction that may signal marital breakdown, such as frequent conflicts, negative communication, or signs of infidelity on social media. However, from the perspective of maqaşid al-shari'ah, the use of this technology must uphold the principles of justice, confidentiality, and the avoidance of greater harm, particularly in safeguarding honor (hifz al-ird) and the privacy of family life. Thus, Al may serve as a tool to help preserve family unity, but its implementation must be regulated within an ethical and sharlah-compliant framework to ensure alignment with maqaşid al-shariah. This study further recommends regulatory reform to accommodate digitai transformation while maintaining the foundational principles of family law.